Cabozantinib after prior checkpoint inhibitor therapy in patients with solid tumors: A systematic literature review. (November 2022) - Graham, Jeffrey; Vogel, Arndt; Cheng, Ann-Lii; Bjarnason, Georg A.; Neal, Joel W.
Highlights: We reviewed clinical outcomes for cabozantinib in patients with solid tumors and prior CPI therapy. Searches identified 21 papers; most (18) reported studies of patients with kidney cancer. Studies consistently reported clinical activity with no new safety signals. Data support the use of cabozantinib after CPI therapy in patients with solid tumors. These findings need to be investigated further in future studies of cabozantinib. Abstract: Introduction: We conducted a systematic literature review to identify evidence for cabozantinib activity in patients with solid tumors after prior checkpoint inhibitor (CPI) therapy. Methods: The review was conducted according to PRISMA guidelines and registered with PROSPERO (CRD42021259873). MEDLINE®, Embase, and the Cochrane Library were searched on 19 May 2021 to identify publications reporting the efficacy/effectiveness and safety/tolerability of cabozantinib in patients with solid tumors who had received prior CPI-based therapy. Publications were screened by one reviewer with uncertainties resolved by a second and/or the full author group. Risk of bias was assessed using Grading of Recommendations Assessment, Development and Evaluation (GRADE) for clinical trials and the Newcastle–Ottawa Scale (NOS) for observational studies. Results: Of 669 publications screened, 21 were eligible: 18 reported data on renal cell carcinoma, and one each for hepatocellular carcinoma, metastatic urothelial carcinoma, and non-small cell lung cancer. Of six trial publications, three reported moderate-quality evidence and three low-quality evidence. Of 15 observational studies, NOS scores ranged from 3 to 6, suggesting a high potential for uncertainty. The studies consistently reported clinical activity for cabozantinib after CPI therapy, across treatment lines and tumor types, with no new safety signals. The findings were limited by the quality and quantity of available data. Conclusion: Cabozantinib appears to have anti-tumor activity after prior CPI therapy in patients with solid tumors. Our results are driven largely by studies in renal cell carcinoma. Evidence from ongoing phase 3 trials is required to establish further the role of cabozantinib after CPI therapy.